Development of an AR-Based Solar System Flashcard Learning Media for Elementary Students Using the MDLC Method - Regania Pasca Rassy; Nurrahmadayeni Nurrahmadayeni; Muhammad Dzulhi Raihan; Latifa Zahra Agustini; Anandi Neina Aeyska Mahdi; Ghina Briliana Fatin Octariana; Luthfiyyah Az Zahro (Jurnal Teknologi Informasi dan Multimedia, 2026)
Understanding the solar system remains challenging for elementary school students due to the abstract, spatial, and three-dimensional nature of astronomical concepts, which are often difficult to convey through conventional learning media. In response to this challenge, this study aims to develop and evaluate an Augmented Reality (AR)–based solar system flashcard learning media to support interactive and meaningful science learning at the elementary level. The learning media was developed using the Multimedia Development Life Cycle (MDLC) method, which consists of concept formulation, design, material collection, assembly, testing, and distribution stages. The AR application integrates three-dimensional planetary visualizations with flashcards to facili-tate concrete representation of abstract concepts and enhance student engagement. The evaluation focused on usability and learning support through User Acceptance Testing (UAT), involving 10 elementary school students and employing a 3-point Likert scale questionnaire. The results indi-cate that the AR-based flashcard media is easy to use, functions reliably, and effectively supports students’ understanding of solar system concepts. Students reported positive experiences in in-teracting with the learning media, suggesting its potential to improve motivation and conceptual comprehension in science learning. This study contributes to the development of innovative digi-tal learning media that promotes inclusive and quality education by integrating emerging tech-nologies into early science instruction. In alignment with Sustainable Development Goal (SDG) 4, the proposed AR-based learning media supports equitable access to engaging educational re-sources and enhances learning quality through interactive, technology-enabled instruction for elementary students.